Burnt fraction sensitivity analysis and 0-D modelling of common rail diesel engine using Wiebe function. (25th March 2017) - Hu, Song; Wang, Hechun; Yang, Chuanlei; Wang, Yinyan
Highlights: The sensitivity of each Wiebe parameter was clearly analysed. An accurate burnt fraction model of each working condition was established. New method of estimating start angle of combustion was proposed. New method of confirming the number of combustion phases was proposed. Abstract: The sensitivity of each Wiebe parameter, namely, the efficiency factor ( a ), form factor ( m ), crank angle of combustion start ( φ 0 ), and combustion crank angle duration ( Δ φ ), is analysed to ensure that these parameters are estimated reasonably and precisely. The sensitivity of each Wiebe parameter is roughly positively associated with the heat release rate normalized by the total fuel energy. The sensitivities of m and φ 0 are larger than the sensitivities of a and Δ φ . m and φ 0 should be estimated carefully, while a and Δ φ can be roughly confirmed. All of sensitivities, the signal-to-noise ratio in cylinder pressure and the certainty in the heat release analysis in the middle stage of combustion are larger than in the early and last stages. Therefore, it is reasonable and necessary to ignore the early and last stages of the combustion process during the confirmation of the Wiebe parameters. The estimated value of φ 0 using the 50-per cent burnt angle, the angle associated with the maximum value of the sensitivity of φ 0 and ignition time are φ 0 – 50, φ 0 – s max and φ ignite . The simulation results indicate that, compared with φ ignite and φ 0 – 50, φ 0 – s max is the most suitable to be set as φ 0 in standard and double Wiebe functions.